Life Cycle Assessment (LCA) in Palm Oil Plantation and Mill with Impact Categories Global Warming Potential, Acidification, and Eutrophication - Sari, Deffi Ayu Puspito; Rahmah , Alifia; Sasongko, Nugroho Adi (International Journal of Membrane Science and Technology, 2023)
The aims are to capture the energy and materials data used to analyze the LCA results in PT. X Study oil palm plantations and mills in Indonesia to find out which stages have the greatest impact on global warming potential (GWP), acidification, and eutrophication. The method used is the LCA approach with the CML-Baseline method. The system boundary in this research is cradle-to-gate on the plantation and mill. The data collected from January to December 2019 exclude the land-use change in plantation, liquid waste and sludge, tools used in plantation, and the amount of water used in plantation and mill, the data proceeded on Microsoft Excel and SimaPro 9.0.0.49. The inventory data collected from plantations are fertilizers, pesticides during plant maintenance, and diesel fuel for transportation, also inventory data collected from mills are electrical energy, steam energy, and diesel fuel. The greatest emissions or hotspots at the plantations are on the usage of fertilizers NPK 15-7-24+1 (384 Kg CO2 equivalent/Ton CPO for GWP, 1.93 Kg SO2 equivalent/Ton for acidification, and 0.65 Kg PO4 equivalent/Ton CPO for eutrophication). The hotspots at the mills for GWP and acidification are on the usage of steam energy boiler no.1 (1,273 Kg CO 2 equivalent/Ton CPO and 10.4 Kg SO 2 equivalent/Ton CPO respectively), and the result for eutrophication is 0.64 Kg PO 4 equivalent/Ton CPO on the usage of electrical energy, Cummins 1 and Cummins 2. The total impact factor is 2.433 Ton CO2 equivalent/Ton CPO for GWP, 16.41 x 10-3 Ton SO2 equivalent/Ton CPO for acidification, and 2,65 x 10-3 Ton PO4 equivalent/Ton CPO for eutrophication.